The Influence of Pedagogic Competency, Leadership of Schools, and Work Motivation Towards Teacher Performance in State Elementary Schools in Medan City - Romy, Elly; Ardansyah, Muhammad; Hambali, Hambali (Universitas Malikussaleh, 2021)
Teacher performance is the result of work achieved when planning, implementing, and assessing learning in schools. The results showed: (1) the effect of pedagogic competence on the work motivation of public elementary school teachers in the Medan City is 0.242; (2) the influence of the principal's leadership on the work motivation of State elementary school teachers in the Medan City is 0.238; (3) the influence of pedagogical competence on the performance of public elementary school teachers in the Medan City is 0.259; (4) the influence of principal leadership on the performance of public elementary school teachers in the Medan City is 0.207; and (5) the effect of work motivation on the performance of public elementary school teachers in the Medan City is 0.200. Based on the results of the study, it was found that the pedagogic competence, principal leadership, and work motivation on teacher performance was 28.7% and the rest was determined by other circumstances.